2013
DOI: 10.1088/1475-7516/2013/09/015
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear curvature perturbation in multi-field inflation models with non-minimal coupling

Abstract: Abstract. Using the δN formalism we consider the non-linear curvature perturbation in multi-field models of inflation with non-minimal coupling. In particular, we focus on the relation between the δN formalism as applied in the conformally related Jordan and Einstein frames. Exploiting results already known in the Einstein frame, we give expressions for the power spectrum, spectral tilt and non-gaussianity associated with the Jordan frame curvature perturbation. In the case that an adiabatic limit has not been… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 58 publications
3
28
0
Order By: Relevance
“…At the classical level it can be shown explicitly that the two frames are related by a 1-to-1 mapping of the fields, and thus lead to the same physics. At the quantum level they give the same results for the 2-and 3-point function [17][18][19][20]. 6 5 The Higgs (and GB, see section 5) contributions to the mid-field regime are negligible in comparison to additional gauge fields and fermions.…”
Section: Compatibility Of Jordan and Einstein Framesmentioning
confidence: 58%
See 2 more Smart Citations
“…At the classical level it can be shown explicitly that the two frames are related by a 1-to-1 mapping of the fields, and thus lead to the same physics. At the quantum level they give the same results for the 2-and 3-point function [17][18][19][20]. 6 5 The Higgs (and GB, see section 5) contributions to the mid-field regime are negligible in comparison to additional gauge fields and fermions.…”
Section: Compatibility Of Jordan and Einstein Framesmentioning
confidence: 58%
“…The two-and three-point functions of the perturbations during inflation are the same in both frames [15][16][17][18][19][20]. We shall demonstrate that this equivalence also holds for the 1-loop effective potential, and, derived from that, for the beta functions.…”
Section: Jcap02(2014)024mentioning
confidence: 66%
See 1 more Smart Citation
“…It was shown that the curvature perturbation is frameindependent [11,12,13,14,15] in the absence of curvature perturbations. Hoewever, framedependent definitions were introduced in the presence of isocurvature perturbations obscuring the equivalence of the two frames [22,23]. Applying the results of the previous section, we can express the perturbations spectrum in terms of the barred fields, which manifestly shows their frame-independence.…”
Section: An Example: Equivalence Of the Curvature And Isocurvature Pementioning
confidence: 99%
“…It is thus rather important to understand how the description of a theory changes from one frame to the other, especially from the Einstein frame to the matter frame, and vice versa. Along this direction, the invariance of physical observables under conformal and disformal transformations is intensively studied in the literature [2,3,[6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%